2018
DOI: 10.3889/oamjms.2018.143
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Deworming and Materno-Perinatal Outcomes in Calabar, Nigeria

Abstract: BACKGROUND:Studies have shown that administration of anthelmintic drugs in pregnancy can reduce the incidence of maternal anaemia; however, data on other maternal and perinatal outcomes are limited.AIM:This study was therefore conducted to evaluate the direct impact of mass deworming on delivery and perinatal outcome.MATERIAL AND METHODS:A total of 560 healthy pregnant women in their second trimester were randomised to receive a single dose of oral mebendazole (500 mg) and placebo. Each participant received th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Despite a few inconsistencies in some studies regarding the antenatal effect of deworming [ 6 ], WHO recommends preventive chemotherapy using single-dose albendazole (400 mg) or mebendazole (500 mg) in pregnant women in areas where the prevalence of anaemia in pregnancy is 40% or higher and the baseline prevalence of hookworm and/or T, trichiura infection is 20% or higher [ 7 ]. In a randomised controlled trial to compare the pregnancy outcomes in Nigeria among those who received 500 mg mebendazole and those who did not, the prevalence of anaemia at 37 weeks gestation and above in the treatment arm was significantly lower than in the placebo group (12.6% vs 29.9%, p < 0.001) [ 8 ]. Similar findings have been reported elsewhere [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite a few inconsistencies in some studies regarding the antenatal effect of deworming [ 6 ], WHO recommends preventive chemotherapy using single-dose albendazole (400 mg) or mebendazole (500 mg) in pregnant women in areas where the prevalence of anaemia in pregnancy is 40% or higher and the baseline prevalence of hookworm and/or T, trichiura infection is 20% or higher [ 7 ]. In a randomised controlled trial to compare the pregnancy outcomes in Nigeria among those who received 500 mg mebendazole and those who did not, the prevalence of anaemia at 37 weeks gestation and above in the treatment arm was significantly lower than in the placebo group (12.6% vs 29.9%, p < 0.001) [ 8 ]. Similar findings have been reported elsewhere [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a developing country study [ 37 ], prenatal deworming was associated with a significant reduction in the risk of low birth weight in countries with a low prevalence of soil-transmitted helminths and a minor reduction in countries with a high prevalence. Prenatal deworming reduced the risk of low birth weight in infants weighing less than 1.5 kg in Peru [ 42 ] and Sri Lanka [ 43 ], but not in infants weighing less than 2.5 kg [ 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The FDA classified mebendazole as a category C drug, which states either studies in animals have shown adverse outcomes on the fetus, and there are no available verified studies in women. In recent studies, reports about firsttrimester exposure to mebendazole are limited; however, researchers have not observed an increased incidence of congenital defects, while used during the second or third trimester (Gyorkos and St-Denis., 2019;Akpan et al, 2018). Drugs should only be an option if the likely advantage justifies the possible risk to the fetus.…”
Section: Adverse Effectmentioning
confidence: 99%